Fluid flow measurement in rotor ventilation ducts. Issue 17 (26th April 2019) - Micallef, Christopher; Degabriele, Joseph; Camilleri, Darren
Abstract : Engineers are constantly developing different ways to cool electrical machines more efficiently. Ventilation ducts/channels are common in the stators of large electrical machines. Lately ventilation ducts on rotors of electrical machines are also being introduced. While measurement of fluid velocities inside stationary ventilation ducts, such as those present in and around the stator core of electrical machines, are relatively easy, measurement of fluid velocities inside rotating ventilation ducts, such as those present on the rotors of electrical machines, is quite challenging. This study describes a method which enables the measurement of fluid velocities inside rotating ducts on the rotor of electrical machines.